The STUDENT INNOVATION IN EXPORT-BASED ENTREPRENEURSHIP BY RECYCLING PLASTIC WASTE INTO HIGH-VALUE PRODUCTS - Tri Septin Muji Rahayu; Aqila Jihan Putri Rahardin Rahardin; Nisa Hidayah Hidayah; Ridho Nurrohman Nurrohman (Journal of Society, Community and Business Development, 2025)
The entrepreneurship project competition is a student creativity program in creating business activities In this activity, the student team practices to create creativity in business products needed by the community (market) made from plastic waste. Through this program, students have ample opportunities to realize creative product ideas, innovate to create new products, and improve their competence, insight and experience in entrepreneurship. This activity was carried out using observation/experiment methods and documentation. The results of the activity include students' ability to carry out the export process, including understanding the dynamics of export document management (Packing list, COO, Invoice, bild of lading and Shipping Instruction, PEB), Marketing kit (company profile, brochure, catalog product, name card), mastering the use of platforms (Google Maps, Go4wordbusiness, Trade Map, Indianmart), export correspondence (Introduction letter, Inquiry, Offering letter, Negotiation letter, Confirming letter, Purchase order, Sales contract). Through this activity, it is hoped that students can carry out export activities in accordance with the correct procedures so that they can be competitive and sustainable by utilizing digital technology. Keywords: Plastic Waste, Export, Entrepreneurship Projects.